REDUCING ENERGY WASTE BY INSTALLING TRANSFORMERS AT THE LOAD CENTER (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Energy waste in electrical systems is a significant challenge, particularly as global electricity demand continues to rise. A substantial portion of this waste occurs in transformers and transmission lines, where energy is lost as heat due to resistance (I²R losses) and other inefficiencies. This article explores the benefits of installing transformers at the load center—closer to where electricity is consumed—as a strategy to reduce energy waste, improve system efficiency, and lower operational costs. By minimizing the length of transmission lines, this approach significantly reduces I²R losses, enhances voltage regulatio, and increases system reliability. Through data analysis, graphs, and charts, the article demonstrates that placing transformers at the load center can cut energy losses by up to 90% compared to centralized systems, resulting in substantial cost savings over time. The findings highlight the importance of optimizing transformer placement as a key step toward achieving sustainable and efficient energy distribution systems. This strategy not only reduces energy waste but also contributes to a more reliable and cost-effective electrical grid, supporting global efforts toward energy conservation and sustainability.